2002
DOI: 10.1093/humrep/17.4.1072
|View full text |Cite
|
Sign up to set email alerts
|

Altered phenotype of HLA-G expressing trophoblast and decidual natural killer cells in pathological pregnancies

Abstract: In pathological pregnancies we show an in-situ altered phenotype of trophoblast and NK cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
2
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 34 publications
3
34
2
3
Order By: Relevance
“…This result is consistent with one study which also found no difference in the expression of HLA-G between women with RM and with normal pregnancies (Patel et al 2003), but is contrary to the findings of Emmer et al (2002) who observed a lower intensity of HLA-G staining of decidual EVTs from women with RM compared with those from women with normal pregnancies. However, Emmer et al (2002) examined samples from only two normal pregnancies and nine women with RM; such a sample size is likely to be inadequate to allow valid conclusions to be drawn. Thus, results from this study suggest that RM is not caused by a lack of HLA-G expression by EVTs.…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with one study which also found no difference in the expression of HLA-G between women with RM and with normal pregnancies (Patel et al 2003), but is contrary to the findings of Emmer et al (2002) who observed a lower intensity of HLA-G staining of decidual EVTs from women with RM compared with those from women with normal pregnancies. However, Emmer et al (2002) examined samples from only two normal pregnancies and nine women with RM; such a sample size is likely to be inadequate to allow valid conclusions to be drawn. Thus, results from this study suggest that RM is not caused by a lack of HLA-G expression by EVTs.…”
Section: Discussionsupporting
confidence: 90%
“…Although no cause is found in the majority of cases, it has been associated with the antiphospholipid syndromes (1), immunological "intolerance" from altered function of endometrial natural killer (NK) cells (2), the polycystic ovary syndrome (3) and insulin resistance (4). A common mechanism for fetal wastage in RPL is defective implantation.…”
Section: Introductionmentioning
confidence: 99%
“…A common mechanism for fetal wastage in RPL is defective implantation. (2) Even when pregnancy following RPL is ultimately successful, placental function may still be compromised, with higher rates of adverse pregnancy outcomes being reported. (5) Abnormal placentation may be associated with high resistance index (RI) in the uterine artery (UA) Doppler waveform, a finding noted to have high predictive value for conditions associated with placental dysfunction such as preeclampsia, fetal growth restriction and placental abruption.…”
Section: Introductionmentioning
confidence: 99%
“…These proteins, also expressed on the surface of extravillous trophoblasts, are involved in inhibition of cytolytic function of uterine natural killer (NK) cells and protect fetal trophoblasts against maternal NK-cell mediated lysis. Two families of inhibitory NK receptors in humans, killer immunoglobulin-like receptors (KIR -belonging to two or three immunoglobulin [Ig] domains) and receptors known as ILT (immunoglobulin-like transcript), confer protection from NK lysis following interaction with HLA-G (Figure 2) (Emmer et al, 2002). Besides modulating the activity of NK cells, the interaction of HLA-G molecules with inhibitory receptors induces apoptosis among activated CD8 + T-cells and induces an expansion of regulatory T (T reg )-cell populations (Rizzo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This points to the potential that the interaction between HLA-G and immunocompetent cells at the placental interface could be critical in determining the outcome of pregnancy. In this regard, it may be critical to look for deviations in these interactions in cases of early pregnancy disorders of unknown etiology (Emmer et al, 2002).…”
Section: Introductionmentioning
confidence: 99%